2021
DOI: 10.3390/cancers13235879
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Core Tissues on Successful Next-Generation Sequencing Analysis of Specimens Obtained through Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration

Abstract: The success rate of next-generation sequencing (NGS) with specimens obtained through endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) among patients with lung cancer as well as the related clinical factors remain unclear. We aimed to determine the optimal number of punctures and core tissues during EBUS-TBNA for NGS in patients with non-small-cell lung cancer (NSCLC) as well as the association of chest computed tomography (CT) and EBUS findings with successful NGS. We retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
(89 reference statements)
0
12
0
Order By: Relevance
“…Another retrospective study also showed that N staging with EBUS-TBNA was significantly correlated with the long-term survival of patients with NSCLC [ 8 ]. In patients with NSCLC, EBUS-TBNA specimens are used to simultaneously search for targeted driver gene mutations using next-generation sequencing [ 9 , 10 ]. Therefore, tumor tissue sampling using EBUS-TBNA is exceedingly important in lung cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Another retrospective study also showed that N staging with EBUS-TBNA was significantly correlated with the long-term survival of patients with NSCLC [ 8 ]. In patients with NSCLC, EBUS-TBNA specimens are used to simultaneously search for targeted driver gene mutations using next-generation sequencing [ 9 , 10 ]. Therefore, tumor tissue sampling using EBUS-TBNA is exceedingly important in lung cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Moreover, the NGS success rate reportedly increased as the number of passes or core tissues obtained increased and also did not change with needle size (22 or 25‐gauge). 15 If, as in our case, core tissue cannot be collected despite a positive finding for malignancy on rapid on‐site evaluation, EBUS‐cryo can complement EBUS‐TBNA, except in settings where cytology specimens are available for NGS. Based on the rate of core tissue obtained per pass, approximately 60%, 16 the range of indications for EBUS‐cryo in clinical practice may be wider than expected.…”
Section: Discussionmentioning
confidence: 79%
“…A meta‐analysis of 21 studies including 1175 patients reported that the pooled proportion of adequate EBUS‐TBNA samples for NGS was 86.5% 14 . Moreover, the NGS success rate reportedly increased as the number of passes or core tissues obtained increased and also did not change with needle size (22 or 25‐gauge) 15 . If, as in our case, core tissue cannot be collected despite a positive finding for malignancy on rapid on‐site evaluation, EBUS‐cryo can complement EBUS‐TBNA, except in settings where cytology specimens are available for NGS.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the median number of specimens collected was three for both slow‐pull and aspiration method groups. Recently, the number of specimens collected (four or more) has been reported to be an essential factor affecting the success of NGS on EBUS‐TBNA specimens 32 . In this study, the NGS success rate may have been further improved by increasing the number of specimens collected to four or more.…”
Section: Discussionmentioning
confidence: 86%
“…Recently, the number of specimens collected (four or more) has been reported to be an essential factor affecting the success of NGS on EBUS-TBNA specimens. 32 In this study, the NGS success rate may have been further improved by increasing the number of specimens collected to four or more. In recent years, the usefulness of the wet suction method, wherein the needle is filled with normal saline solution and a negative pressure is applied, 20 and the combination of the fanning and slow-pull methods, wherein the needle is stroked while changing its direction within the lesion, 33 has been reported for EUS-FNA of pancreatic masses.…”
Section: Discussionmentioning
confidence: 94%